Sensor eletroquímico à base de óxido de grafeno reduzido para análise simultânea de p-benzoquinona e resorcinol em amostras ambientais - OLIVEIRA, Eleilde de Sousa (2021)
The contamination of the environment by organic compounds derived from benzene represents a serious problem today. p-benzoquinone (BQ) and resorcinol (RS) comprise compounds belonging to this class and are considered contaminants of soil and natural waters. Therefore, the monitoring of these residues is of relevant scientific interest. The present work proposes an electrochemical sensor based on reduced graphene oxide (GCE/rGO), for the simultaneous determination of BQ and RS in soil and water from gas stations and seawater. The surface of the GCE/rGO was characterized by Fourier Transform Infrared Spectroscopy (FT-IR) and the electrochemical properties of the sensor were studied via Chronoamperometry, Cyclic Voltammetry (CV) and Electrochemical Impedance Spectroscopy (EIE). Using the Square Wave Voltammetry (SWV) technique, the GCE/rGO sensor was evaluated in the electroanalytical aspect. After the optimization of the experimental parameters, the following best conditions were found: frequency = 10 mV; amplitude = 20 mV; step potential = 2 mV. In these optimized conditions, the proposed sensor presented an excellent electrochemical performance for the oxidation of BQ and RS showing a linear behavior between the anodic peak currents and the concentrations for both analytes in the range of 12 to 100 µmol.L -1 . Through the calibration curves LD and LQ values were calculated (BQ: LD = 0.37 µmol.L -1 and LQ = 1.23 µmol.L -1 ; RS: LD = 0,81 µmol L-1 and LQ = 2.71 µmol.L -1 ). The application of the new method via fortification in real samples presented excellent accuracy, considering an average recovery greater than 99% in the applied samples (soil, fuel station water, and sea water). The precision (relative standard deviation) was 0.10% for BQ and 0.36% for RS. The good results obtained indicate, from the analytical and statistical aspect, that the proposed sensor is suitable for the simultaneous determination of BQ and RS in environmental soil and water samples.